2021
DOI: 10.1007/s11904-021-00550-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis in Implementation Science: a Research Agenda and Call for Wider Application

Abstract: Purpose of Review Cost-effectiveness analysis (CEA) can help identify the trade-offs decision makers face when confronted with alternative courses of action for the implementation of public health strategies. Application of CEA alongside implementation scientific studies remains limited. We aimed to identify areas for future development in order to enhance the uptake and impact of model-based CEA in implementation scientific research. Recent Findings Important questions remain about how to broadly implement ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…For example, Cidav et al (2020) advanced a theoretical framework to incorporate cost estimates into implementation evaluation [ 23 ]. Most research on this subject was recent: 12 of the 23 studies were published during the last 2 years of the review [ 17 , 18 , 22 25 , 27 – 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Cidav et al (2020) advanced a theoretical framework to incorporate cost estimates into implementation evaluation [ 23 ]. Most research on this subject was recent: 12 of the 23 studies were published during the last 2 years of the review [ 17 , 18 , 22 25 , 27 – 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, one qualitative evaluation of decision-makers operating in a range of service settings found that the costs of pre-implementation activities, including changing workflow, modifying contracts, and building infrastructure, were predominant factors in the decision of whether or not to implement various evidence-based practices [ 8 ]. Implementation costs often are overlooked in economic evaluations [ 9 ], and there are few economic evaluations that compare the value of implementation strategies, incorporating such implementation costs [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further economic evaluations of public health implementation interventions have emerged since this review [45][46][47][48][49][50]; however, the field of work remains small and studies are highly variable by topic, research design, setting and outcome measure(s). Cost evaluations of public health implementation interventions, especially via cost-effectiveness estimates, are needed to enhance understanding and ultimately to increase the uptake of evidence-based practices across settings [41,43,51,52]. Given the established evidence base demonstrating the cost-effectiveness of increasing physical activity in schools [18][19][20][21][22], we sought to determine the efficiency of the additional investment required to increase policy implementation.…”
Section: Introductionmentioning
confidence: 99%